Putative COVID-19 therapies imatinib, lopinavir, ritonavir, and ivermectin cause hair cell damage: A targeted screen in the zebrafish lateral line - Coffin, Allison B.; Dale, Emily; Doppenberg, Emilee; Fearington, Forrest; Hayward, Tamasen; Hill, Jordan; Molano, Olivia (Frontiers in Cellular Neuroscience, 2022)
The biomedical community is rapidly developing COVID-19 drugs to bring much-need therapies to market, with over 900 drugs and drug combinations currently in clinical trials. While this pace of drug development is necessary, the risk of producing therapies with significant side-effects is also increased. One likely side-effect of some COVID-19 drugs is hearing loss, yet hearing is not assessed during preclinical development or clinical trials. We used the zebrafish lateral line, an established model for drug-induced sensory hair cell damage, to assess the ototoxic potential of seven drugs in clinical trials for treatment of COVID-19. We found that ivermectin, lopinavir, imatinib, and ritonavir were significantly toxic to lateral line hair cells. By contrast, the approved COVID-19 therapies dexamethasone and remdesivir did not cause damage. We also did not observe damage from the antibiotic azithromycin. Neither lopinavir nor ritonavir altered the number of pre-synaptic ribbons per surviving hair cell, while there was an increase in ribbons following imatinib or ivermectin exposure. Damage from lopinavir, imatinib, and ivermectin was specific to hair cells, with no overall cytotoxicity noted following TUNEL labeling. Ritonavir may be generally cytotoxic, as determined by an increase in the number of TUNEL-positive non-hair cells following ritonavir exposure. Pharmacological inhibition of the mechanotransduction (MET) channel attenuated damage caused by lopinavir and ritonavir but did not alter imatinib or ivermectin toxicity. These results suggest that lopinavir and ritonavir may enter hair cells through the MET channel, similar to known ototoxins such as aminoglycoside antibiotics. Finally, we asked if ivermectin was ototoxic to rats in vivo. While ivermectin is not recommended by the FDA for treating COVID-19, many people have chosen to take ivermectin without a doctor’s guidance, often with serious side-effects. Rats received daily subcutaneous injections for 10 days with a clinically relevant ivermectin dose (0.2 mg/kg). In contrast to our zebrafish assays, ivermectin did not cause ototoxicity in rats. Our research suggests that some drugs in clinical trials for COVID-19 may be ototoxic. This work can help identify drugs with the fewest side-effects and determine which therapies warrant audiometric monitoring.